Chest Magnetic Resonance Imaging Decreases Inter-observer Variability of Gross Target Volume for Lung Tumors - Basson, Laurent; Jarraya, Hajer; Escande, Alexandre; Cordoba, Abel; Daghistani, Rayyan; Pasquier, David; Lacornerie, Thomas; Lartigau, Eric; Mirabel, Xavier (Frontiers in Oncology, 2019)
Purpose: PET/CT is a standard medical imaging used in the delineation of gross tumor volume (GTV) in case of radiation therapy for lung tumors. However PET/CT could present some limitations such as resolution and standardized uptake value threshold. Moreover chest MRI has shown good potential in diagnosis for thoracic oncology. Therefore, we investigated the influence of chest MRI on inter-observer variability of GTV delineation Methods and Materials: Five observers contoured the GTV on CT for 14 poorly defined lung tumors during three contouring phases based on true daily clinical routine and acquisition: CT phase, with only CT images; PET phase, with PET/CT; and MRI phase, with both PET/CT and MRI. Observers waited at least one week between each phases to decrease memory bias. Contours were compared using descriptive statistics of volume, coefficient of variation (COV), and Dice similarity coefficient (DSC). Results: MRI phase volumes (median 4.8 cm3) were significantly smaller than PET phase volumes (median 6.4 cm3, p=0.015), but not different from CT phase volumes (median 5.7 cm3, p=0.30). The mean COV was improved for the MRI phase (0.38) compared to the CT (0.58, p=0.024) and PET (0.53, p=0.060) phases. The mean DSC of the MRI phase (0.67) was superior to those of the CT and PET phases (0.56 and 0.60 respectively; p<0.001 for both). Conclusions: The addition of chest MRI seems to decrease inter-observer variability of GTV delineation for poorly defined lung tumors compared to PET/CT alone and should be explored in further prospective studies.